Apocalypse Then : American Intellectuals and the Vietnam War, 1954-1975. - Tomes, Robert R. (NYU Press, 1998)
Prior to the Vietnam war, American intellectual life rested comfortably on shared assumptions and often common ideals. Intellectuals largely supported the social and economic reforms of the 1930s, the war against Hitler's Germany, and U.S. conduct during the Cold War. By the early 1960s, a liberal intellectual consensus existed. The war in Southeast Asia shattered this fragile coalition, which promptly dissolved into numerous camps, each of which questioned American institutions, values, and ideals. Robert R. Tomes sheds new light on the demise of Cold War liberalism and the development of the.